Factores que motivan el uso de la biblioteca universitaria (The motivation’s factors to library university use) - Hernández, José Segoviano; Palomo González, Miguel Ángel (Universidad Autonoma de Nuevo Leon, 2010)
Abstract: This paper presents the results of a documentary search about factors that motivate the use of university library. Literature about these factors was not found, either not standards or indicators used to measure those factors’ impact. On the other side, evidence was found about the decrease in library attendance, reported by the university libraries themselves; however, no evidence about the causes of this phenomenon was found. In such a context, this article presents a research project that will be applied in 3 universities at Northeast Mexico, in which a methodology to identify and analyze motivation in students to use the university library is proposed.